The effect of polyurethane foam glue on the strength and deformability of aerated concrete masonry when using it as a masonry mortar - Dzhamuev Bulat (E3S Web of Conferences, 2023)
The article presents the results of experimental studies of masonry made of cellular concrete blocks of autoclave hardening YTONG produced by JSC «Kcell-Aeroblock-Center» on the adhesive composition (polyurethane glue) Dryfix (POLYPAG AG). The tests included comprehensive studies of the strength and deformability of masonry walls made of cellular concrete blocks, under various types of stress state of structures: central and off-center compression of masonry walls, axial tension on bandaged and unbound seams, tensile bending on bandaged and unbound seams, shear with an assessment of tangential adhesion. Tests have confirmed the inconsistency of the technology of laying blocks of cellular concrete on the adhesive composition of Dryfix with incomplete filling of seams. This technology has a significant impact on the strength of the masonry during bending: the adhesion of the blocks to each other with such an adhesive composition applied to the surface of the block is significantly lower than the value obtained when testing the blocks for axial tension. According to the results of the experiments, the value of the temporary resistance to axial stretching along the unbound section (normal adhesion) of the masonry, the values of the calculated resistance of the masonry to stretching during bending along the unbound and tied sections, as well as the value of the calculated resistance of the masonry under central compression were determined.